Educational technology on developing humanistic character in midwifery education curriculum - Diniati Sukmana; Ari Indra Susanti (Curricula: Journal of Curriculum Development, 2025)
Various aspects of life, including education, have been significantly impacted by technological advances. The principles of humanistic learning are applied to achieve quality and meaningful learning outcomes. Curriculum development has become a crucial factor in enhancing the quality of midwifery education and research. Strengthening regulations in the development of midwifery policies has influenced the evolution of midwifery education curricula. This article aims to review the role of educational technology in developing humanistic character in the midwifery curriculum. The method used is a scoping review. Data were obtained from 9 articles accessed through the Google Scholar databases. The results of the study show that the role of educational technology in developing humanist character in the midwifery education curriculum includes flexibility and accessibility of learning, empowerment of social and emotional skills, simulation development and practical learning in a professional context, increased collaboration and student involvement, and providing direct feedback. In conclusion, the integration of technology into the midwifery education curriculum is an important step in preparing a generation of professionals who are not only technically skilled, but also have high moral character in facing future professional challenges.   Abstrak Berbagai aspek kehidupan, termasuk pendidikan telah terpapar kemajuan teknologi. Prinsip-prinsip pembelajaran humanistik diterapkan untuk mencapai hasil pembelajaran berkualitas dan bermakna. Pengembangan kurikulum telah menjadi faktor yang berperan penting dalam meningkatkan kualitas pendidikan dan penelitian kebidanan. Penguatan regulasi dalam pengembangan kebijakan di bidang kebidanan telah mempengaruhi pengembangan kurikulum pendidikan bidan. Artikel ini bertujuan untuk meninjau peran teknologi pendidikan dalam pengembangan karakter humanis pada kurikulum kebidanan. Metode yang digunakan adalah scoping review. Data diperoleh dari 9 artikel yang diakses melalui database google scholar. Hasil penelitian menunjukkan peran teknologi pendidikan dalam pengembangan karakter humanis pada kurikulum pendidikan kebidanan meliputi fleksibilitas dan aksesibilitas pembelajaran, pemberdayaan keterampilan sosial dan emosional, pengembangan simulasi dan pembelajaran praktis dalam konteks profesional, peningkatan kolaborasi dan keterlibatan peserta didik, dan pemberian umpan balik secara langsung. Kesimpulannya, integrasi teknologi dalam kurikulum pendidikan kebidanan merupakan langkah penting dalam mempersiapkan generasi profesional yang selain terampil secara teknis, juga berkarakter moral yang tinggi dalam menghadapi tantangan profesi di masa depan. Kata Kunci: karakter humanis; kurikulum; teknologi pendidikan